Analisis Pemanfaatan Briket Tempurung Kenari Sebagai bahan Bakar - Nur Asmiani; Alfian Nawir; Muhammad Ainul Az; Suriyanto Bakri; Agus A Budiman; Firman Nullah Yusuf (Jurnal Geomine, 2022)
Walnuts is one of the bio-masses whose quantity is quite abundant but its use has not been optimized. One of them is the walnut shell as one of the fuel replacement solutions which is increasingly thinning. This study aims to produce walnut shell briquettes that have economic value and are able to replace or equal to coal briquettes. The briquettes are grouped in 3 samples. Sample I with a composition of 100% walnut shell, sample II with a composition of 50%: 50% between shell walnuts with coal while sample III with a composition of 100% coal. Furthermore, for samples with walnut shell compositions, sample I and sample II are divided into 3 sizes, namely mesh 28, mesh 65 and mesh 80. In the first sample is a benchmark for samples II and III that will be seen by each composition they have like nilia calories, ash content, total sulfur flying content and water content. The process of making briquettes with 250 gr walnut shell composition, 50 gr tapioca flour and 100 ml water. From the results of this study, the authors get the results that canary shell briquettes are able to compete and replace coal briquettes can be seen in the grain size of 65 walnut shell briquettes.